A utilização do software Sábio: uma aventura ecológica como ferramenta didática no Ensino de Ciências Ambientais - OLIVEIRA, Ney Cristina (2022)
The use of educational technology in the current context of educational institutions is fundamental for the modernization of Brazilian education, in this sense, the present work aimed to stimulate children's awareness of environmental education through educational games. This work presents the process of development and application of an environmental education game called Sage - An Ecological Adventure. The use of the game promoted, among the students, an interest in combating the environmental problems faced in Ananindeua / PA, in the metropolitan region of Belém. year. Questionnaires containing questions regarding the degree of difficulty of the game and the environmental problems existing in the city were distributed to students. After the applicability of the game and the answers obtained with the questionnaires, it was possible to observe that the students actively participated in each phase of the game and understood the importance of caring for the environment.